Improving the Mechanism of Innovation Planning with the System-Transdisciplinary Approach - T. Volkov, Andrey; M. Gureev, Pavel; N. Grishin, Valentin; N. Dunenkova, Elena; I. Onishchenko, Svetlana; V. Metelkin, Pavel (International Journal of Psychosocial Rehabilitation, 2020)
The article considers the potential of using system-transdisciplinary tools in innovation management. The relevance of this research is determined by the fact that innovation management has no methods or techniques for estimating the temporal characteristics of innovation as a process. In addition, the scientific community has come to understand that the complex and multi-factorial systems used in research, which definitely include organizational systems, as well as disciplinary, inter-, and multidisciplinary methods, have exploited almost all their potential. Consequently, further scientific advances objectively require new methods of exploring the mechanism of a company’s development. Application of a multiplex transdisciplinary tool in planning enabled the development of an approach that can be used to determine the duration of different stages of the innovation process. This means not only efficient distribution of the company’s resources over time but also creating a justified roadmap for innovation. The retrospective analysis of implementing innovations in several enterprises, conducted by the authors, proved the validity of the proposed approach to planning the development of the company within the system-transdisciplinary methodology.